Clinical features of unilateral Wallenberg syndrome and respiratory failure - GAO Lin⁃zhi; ZHANG Ai⁃juan; ZHANG Ai⁃yuan; MA Meng⁃bing; ZHONG Meng⁃fei (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Objective To summarize the clinical features of unilateral Wallenberg syndrome. Methods and Results The clinical data of 28 patients with unilateral Wallenberg syndrome admitted to Shengli Oilfield Central Hospital and Weifang People′s Hospital from March 2005 to November 2021 were retrospectively analyzed. Clinical manifestations were pain and temperature disturbance in 26 cases (92.86%), ataxia in 24 cases (85.71%), numbness in 21 cases (75%), dizziness in 20 cases (71.43%); MRI showed dorsolateral medulla oblongata infarction lesion in all patients, 9 cases (32.14%) with lesions located in the rostral medulla oblongata, 7 cases (25%) in the central region and 12 cases (42.86%) in the caudal region; CTA showed there were responsible arteries in 27 cases (96.43%), including vertebral artery stenosis (15 cases, 53.57%), posterior inferior cerebellar artery occlusion (10 cases, 35.71%), bilateral vertebral artery occlusion and unilateral vertebral artery dissection (one case each, 3.57%). Eleven cases (39.29%) were treated with intravenous thrombolysis, including 3 cases with bridging vertebral artery stent implantation and 17 cases (60.71%) with conservative treatment. 19 cases (67.86%) had a good prognosis, while 9 cases (32.14%) had a poor prognosis. There are 5 cases (17.86%) complicated with respiratory failure, one case with good prognosis after symptomatic treatment, one case of ventilator assisted ventilation, one case was severely disabled, and 2 cases were dead. Conclusions Unilateral Wallenberg syndrome has multiple clinical manifestations, imaging examination has great significance for clear diagnosis, some patients may develop respiratory failure and their respiratory function should be closely monitored.